Etika Islam Inklusif dan Mobilitas Ekonomi: Studi Kasus terhadap Pedagang Muslim Pasar Pontang, Ambulu, Jember: Inclusive Islamic Ethics and Economic Mobility: A Case Study of Muslim Traders at Pontang Market, Ambulu, Jember - M. Saiful Anam (Fenomena, 2018)
This study examines the phenomenon of vertical economic mobility among Muslim traders at Pontang Market, Ambulu, Jember, who initially started with minimal capital yet managed to improve their economic standing. The research addresses how Islamic religious ethics influence this mobility process, employing theoretical frameworks of economic mobility, Islamic business ethics, and Weberian perspectives on religion and economic dynamics. A qualitative method was applied, integrating religious-ethical, phenomenological, and sociological approaches. Data were collected through in-depth interviews, participant observation, and document analysis, with purposively selected traders as subjects. The findings reveal a three-phase pattern of economic mobility: initial struggle, early progress, and advanced development. The traders adhere to a religious-ethical system rooted in tawhid, which generates value principles such as hard work, perseverance, thoroughness, honesty, discipline, patience, courage, and resilience. These principles translate into ethical norms guiding their business conduct. The study concludes that Islamic religious ethics play a significant role in the economic mobility of Pontang Muslim traders, though not as a sole factor, and recommends further research involving broader social aspects. Penelitian ini mengkaji fenomena mobilitas ekonomi vertikal pada pedagang Muslim Pasar Pontang, Ambulu, Jember, yang awalnya bermodal minim namun mampu meningkatkan taraf ekonomi. Fokus penelitian adalah bagaimana peran etika religius Islam dalam proses mobilitas tersebut, dengan menggunakan kerangka teori mobilitas ekonomi, etika bisnis Islam, dan perspektif Weber tentang hubungan agama dan dinamika ekonomi. Metode kualitatif diterapkan dengan pendekatan etik-religius, fenomenologis, dan sosiologis. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen, dengan subjek dipilih secara purposif. Hasil penelitian menunjukkan pola tiga tahap mobilitas ekonomi: awal perjuangan, perkembangan awal, dan lanjutan. Para pedagang menganut sistem etik-religius yang bertumpu pada tauhid, melahirkan prinsip nilai seperti kerja keras, ketelatenan, ketekunan, kejujuran, disiplin, kesabaran, keberanian, dan keuletan, yang kemudian menjadi norma etik dalam berusaha. Kesimpulannya, etika religius Islam berperan signifikan dalam mobilitas ekonomi pedagang Pasar Pontang, meskipun bukan satu-satunya faktor, dan direkomendasikan penelitian lanjutan dengan cakupan aspek sosial yang lebih luas.